Beauty, fashion and elegance in Colombia view through the magazine Cromos, 1916- 1929 (Tzintzun, Revista de Estudios Históricos, 2019)
The text focuses on the understanding of the female beauty canons registered and publicized by Cromos magazine, a colombian publication of national circulation that promoted aesthetic ideals on the body of women to highlight their femininity. The article is attached to the field of cultural history that allowscharacterizing expressions and representations, in this case, focused on the recognition of the meanings of beauty and elegance, where beauty is an attributethat is achieved by combining harmony and normality, which also it becomes a consumer good; Beauty during this period (1916-1929) is associated with a youthful appearance: white complexion, smooth skin and hair without gray hair. While elegance is reflected in the expression of the face and the slender figure, which is related to the appearance of a modern woman, that is, the woman who must face labor and educational roles.